Available Compounds With Therapeutic Potential Against COVID-19: Antimicrobial Therapies, Supportive Care, and Probable Vaccines - Kumar, Rajnish; Srivastava, Janmejai Kumar; Singh, Rachana; Siddiqui, Mohammed Haris; Mansouri, Rasha A.; Abdulhakim, Jawaher A.; Bin-Jumah, May N.; Alkahtani, Saad; Abdel-Daim, Mohamed M.; Uddin, Md. Sahab (Frontiers in Pharmacology, 2020)
The recent outbreak of the COVID-2019 (coronavirus disease 2019) due to the infectious severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has realized the requirement of alternative therapeutics to mitigate and alleviate this lethal infection. These alternative therapies are effective when they are started at the initial stage of the infection. Some drugs that were used in previous other related infections SARS-CoV-2003 and Middle East respiratory syndrome coronavirus (MERS-CoV)-2012 could be potentially active against currently emerging SARS-CoV-2. This fact imparts some rationale of current interventions, in the absence of any specific therapeutics for SARS-CoV-2. It is imperative to focus on the available antimicrobial and adjunct therapies during the current emergency state and overcome the challenges associated with the absence of robust controlled studies. There is no established set of drugs to manage SARS-CoV-2 infected patients. However, closely following patients' conditions and responding with the dosage guidelines of available drugs may significantly impact our ability to slow down the infection. Of note, it depends upon the condition of the patients and associated comorbid; therefore, the health workers need to choose the drug combinations judiciously until COVID-19 specific drug or vaccine is developed with the collective scientific rigor. In this article, we reviewed the available antimicrobial drug, supportive therapies, and probable high importance vaccines for the COVID-19 treatment.